Eczematous Drug Eruptions due to Bacampicillin - HARADA, Shotaro; YOON, Sook hyang; YOON, Hong il (Skin research, 1985)
A 55-year-old man had been orally administered bacampicillin due to prostatitis, followed by generalized eczematous eruptions. Patch tests with 14 derivatives of penicillin showed a cross sensitivity, while none with 7 of cephalosporins.